2012
DOI: 10.1002/pbc.24059
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Wilms tumors (WT) treated with the SIOP 93 protocol in France: Epidemiological survey and patient outcome

Abstract: Results of this study demonstrate a favorable outcome of patients with bilateral WT receiving an individual treatment program. With a tailored approach to treatment according to the tumor response, 77% of our patients were operated before the third month of preoperative chemotherapy. In spite of good survival, 14% of our patients have ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 24 publications
9
52
1
Order By: Relevance
“…This equals recent data published by NWTS4 and NWTS5 with 82.1 % OS after 10 years [ 17 ] , by the French group with 89.5 ± 6.5 % after 5 years [ 18 ] and by the Italian group with 80 ± 5 % OS after 4 years [ 9 ] . And it is signifi cantly superior to the survival rates of 69 % reported earlier by the UKCCSG's study [ 11 ] and of 64 % by the SIOP [ 5 ] .…”
Section: Patients With a Localized Disease Without Pretreatment And supporting
confidence: 89%
“…This equals recent data published by NWTS4 and NWTS5 with 82.1 % OS after 10 years [ 17 ] , by the French group with 89.5 ± 6.5 % after 5 years [ 18 ] and by the Italian group with 80 ± 5 % OS after 4 years [ 9 ] . And it is signifi cantly superior to the survival rates of 69 % reported earlier by the UKCCSG's study [ 11 ] and of 64 % by the SIOP [ 5 ] .…”
Section: Patients With a Localized Disease Without Pretreatment And supporting
confidence: 89%
“…In the SIOP−2001 study, patients with bilateral disease received preoperative chemotherapy including vincristine and actinomycin D until NSS was deemed feasible, with response evaluations performed every 4 weeks. However, several studies have shown that prolonged preoperative chemotherapy is often ineffective (especially as many bilateral tumours are the chemotherapy-insensitive stromal subtype) and could even result in an increased risk of the presence of anaplasia, disease progression, and development of metastases 31,32,34 . Thus, the UMBRELLA protocol limits preoperative chemotherapy to a maximum of 12 weeks, with time intervals for evaluation fixed to 6 weeks, to be comparable with the COG approach for future studies.…”
Section: Cmn Rccmentioning
confidence: 99%
“…11, 12, 34, 35 An overriding goal was to improve EFS balanced with conservation of renal tissue. Our goal was to have at least 50% of patients undergo bilateral nephron-sparing surgery (NSS).…”
Section: Discussionmentioning
confidence: 99%